Comparative Transcriptome Analysis Revealed the Freezing Tolerance Signaling Events in Winter Rapeseed (Brassica rapa L.) - Wu, Wangze; Yang, Haobo; Xing, Peng; Dong, Yun; Shen, Juan; Wu, Guofan; Zheng, Sheng; Da, Lingling; He, Jiangtao; Wu, Yujun (Frontiers in Genetics, 2022)
Winter rapeseed (Brassica rapa L.) is an important oilseed crop in northwest China. Freezing stress severely limits its production and geographical distribution, and frequent extreme freezing events caused by climate change are increasing the chances of winter freeze-injury. However, the underlying mechanism of B. rapa response to freezing stress remains elusive. Here, B. rapa genome (v3.0) was used as a reference for the comparative transcriptomic analysis of Longyou 6 and Tianyou 2 (strong and weak cold tolerance, respectively) under different freezing stress. Before and after freezing stress, 5,982 and 11,630 unique differentially expressed genes (DEGs) between two cultivars were identified, respectively. After freezing stress, the GO terms in Tianyou 2 were mainly involved in “macromolecule biosynthetic process”, and those in Longyou 6 were involved in “response to stimulus” and “oxidoreductase activity”. Morphological and physiological results indicated that Longyou 6 retained a higher basal freezing resistance than Tinayou 2, and that cold acclimation could strengthen the basal freezing resistance. Freezing stress could activate the MAPK signal cascades, and the phosphorylation level of Longyou 6 showed a higher increase in response to freezing treatment than Tianyou 2. Based on our findings, it was speculated that the cell membrane of B. rapa perceives external signals under freezing stress, which are then transmitted to the nucleus through the cold-activated MAPK cascades and Ca2+-related protein kinase pathway, thus leading to activation of downstream target genes to enhance the freezing resistance of B. rapa.